X(X-2)-3X=0 因式分解法
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/04 00:35:44
X(X-2)-3X=0因式分解法X(X-2)-3X=0因式分解法X(X-2)-3X=0因式分解法x^2-2x-3x=0x^2-5x=0x(x-5)=0X(X-2)-3X=0x(x-2-3)=0x(x-
X(X-2)-3X=0 因式分解法
X(X-2)-3X=0 因式分解法
X(X-2)-3X=0 因式分解法
x^2-2x-3x=0
x^2-5x=0
x(x-5)=0
X(X-2)-3X=0
x(x-2-3)=0
x(x-5)=0
所以 x=0 或 x=5
4x^2-3x=0因式分解法
因式分解法3(x-2)=x(x-2)
因式分解法:2(x-3)²+(3x-x²)=0
X(X-2)-3X=0 因式分解法
(x+5)方+3(x+5)-4=0用因式分解法 9(x-1)方=(2x+1)方 用因式分解法
(2x-3)^2-81=0因式分解法
(2x+1)(x-2)=0因式分解法
因式分解法 X平方+3X-4=0
4x²-3x=0因式分解法
x²+2x=0 因式分解法
因式分解法x的平方-x-2=0
(X+2)²=3(X+2) 因式分解法
3x^2=7x因式分解法
请问(2-3x)+(3x-2)平方=0 用因式分解法
(2x-3)的平方-2x+3=0因式分解法,
用因式分解法解3(x+2)²-6(x+2)=0
3(x+2)(x-2)=0用因式分解法解
4(x+2)²-9(x-3)²=0(因式分解法)